Barriers to collecting student participation and completion data for a national STEM education grant program in the United States: a multiple case study - Robert J. Ruhf; Cody T. Williams; Megan Zelinsky; Lyssa Wilson Becho (SpringerOpen, 2022)
Abstract Background Billions of dollars are spent annually on grant-funded STEM (science, technology, engineering, and mathematics) education programs. These programs help students stay on track toward STEM careers when standard educational practices do not adequately prepare them for these careers. It is important to know that reliable and accurate student participation and completion data are being collected about these programs. This multiple case study investigates how student data are collected and reported for a national STEM education program in the United States, the National Science Foundation (NSF) Advanced Technological Education (ATE) program. Our overall aim is to provide insights to funding agencies, STEM education faculty, and others who are interested in addressing issues related to the collection and reporting of student participation and completion data within their own contexts. Emphasis is placed on the barriers encountered in collecting participation and completion data, particularly with regard to unduplicated participation counts and marketable credential data. The ATE program was selected for this study because there is already a mechanism (known as the ATE Survey) in place for annually collecting systematic data across all projects within the program. Results A multiple case study, including interviews of primary investigators, allowed for in-depth analysis of the ATE Survey's point-in-time data on project-level participation in various activities, and for identification of the following barriers to tracking student-level data: lack of time and help to gather these data, lack of a consistent system for tracking students across different institutions, and a perceived lack of guidance from the funding agency about what data to track. We also saw that different data are needed from different projects to determine a project's true impact. Defining "success" the same way across all projects is inadequate. Conclusions Although, due to the limited sample size, these findings cannot be generalized to the larger ATE population, they provide specific insights into the various barriers that projects encounter in collecting participation and completion data.